2002
DOI: 10.1182/blood-2002-03-0772
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment cytogenetic abnormalities are predictive of induction success, cumulative incidence of relapse, and overall survival in adult patients with de novo acute myeloid leukemia: results from Cancer and Leukemia Group B (CALGB 8461)

Abstract: We analyzed prospectively 1213 adults with de novo acute myeloid leukemia (AML) to ascertain the prognostic impact of cytogenetic abnormalities on complete remission (CR) rate, 5-year cumulative incidence of relapse (CIR), and 5-year overall survival (OS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

47
1,045
20
44

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,427 publications
(1,156 citation statements)
references
References 48 publications
47
1,045
20
44
Order By: Relevance
“…Among these are certain secondary cytogenetic aberrations, leukocytosis, CD56 expression and extramedullary manifestations. Review of the literature found that some suggested indicators, most notably CD56 9 and extramedullary involvement, 10 were identified in a single or relatively small studies; others were based on the patients treated with different protocols [11][12][13][14] or included secondary leukemia, 15 rendering it difficult to compare and draw consistent conclusions. This is particularly true regarding implications of additional cytogenetic aberrations.…”
mentioning
confidence: 99%
“…Among these are certain secondary cytogenetic aberrations, leukocytosis, CD56 expression and extramedullary manifestations. Review of the literature found that some suggested indicators, most notably CD56 9 and extramedullary involvement, 10 were identified in a single or relatively small studies; others were based on the patients treated with different protocols [11][12][13][14] or included secondary leukemia, 15 rendering it difficult to compare and draw consistent conclusions. This is particularly true regarding implications of additional cytogenetic aberrations.…”
mentioning
confidence: 99%
“…Currently, cytogenetic findings provide the most important prognostic information and are used to guide risk-adapted treatment strategies [2]. Cytogenetically normal AML (CN-AML) represents 40-50 % of all AML cases and currently is considered separate entity in WHO classification [3].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostically bad karyotypic abnormalities, also present in B15% of patients, include deletion of chromosome 7, deletion of chromosome 5q and more than three chromosomal abnormalities. 4,5 Other karyotypic abnormalities that have an unclear effect on prognosis have been observed, including trisomy 8 and trisomy 21d. These abnormalities are generally considered to be in the intermediate-risk prognosis category along with normal karyotype.…”
Section: Introductionmentioning
confidence: 99%
“…These abnormalities are generally considered to be in the intermediate-risk prognosis category along with normal karyotype. The identification of these markers led to the development of cytogenetic risk classification systems by several cooperative groups internationally, including the Cancer and Leukemia Group B, 5 Eastern Cooperative Oncology and Southwest Oncology Groups, 6 the UK Medical Research Council 2 and Frö hling et al 4 in Germany.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation